THE INFLUENCE OF INSTITUTIONAL OWNERSHIP TOWARDS EXECUTIVE COMPENSATION CONSIDERED BY THE PERFORMANCE OF THE COMPANY - Maharani, Wahyu Puspita; Utami, Evy Rahman (Universitas Muhammadiyah Malang)
This study aims to analyze the effect of institutional ownership towards executive compensation mediated by company performance. This study used manufacturing companies listed on the Indonesia Stock Exchange during the period 2015-2017 as the sample. The sample selection method used purposive sampling so that sampling is in accordance with the criteria that have been set by the researcher. The number of samples used in this study were 209 companies. The analytical tool used was multiple regression analysis and path analysis to measure the mediating variables. The results of this study indicated that institutional ownership has a positive and significant effect on company performance, institutional ownership did not directly influence executive compensation and the company's performance variable was able to mediate the relationship of institutional ownership to executive compensation.